Implementation of Universal Human Rights Values Based on the Universal Declaration of Human Rights in Indonesia - Selyawati, Ni Putu (Universitas Negeri Semarang, 2017)
In the era of globalization where law enforcement is desired based on a good or standard legal framework (good legal system), a country if it enforces laws that violate human rights will definitely be criticized and even isolated by other countries as members of society. a world that is not committed to human rights. The UN Human Rights Declaration or Universal Declaration of Human Rights is considered as an important instrument in the universal protection of human rights. This paper discusses how the human rights values contained in the declaration are applied in Indonesia.